2014
DOI: 10.1108/vine-04-2013-0024
|View full text |Cite
|
Sign up to set email alerts
|

Usage, benefits and barriers of human resource information system in universities

Abstract: Purpose -The purpose of this paper is to examine the university teaching staff's perception about functions, benefits and barriers of human resource information system (HRIS). It also aims to explore the relevance of attitudinal/demographic diversity with focused HRIS dimensions. Design/methodology/approach -A 26-item questionnaire was developed on the basis of similar research studies. Responses were collected through electronic mail from 90 faculty members of seven state universities in India. Descriptive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 75 publications
4
63
0
1
Order By: Relevance
“…As demonstrated by Tables 1, 2, in the context of HRIS, the TAM and UTAUT models have been combined with others including, for example, the Yale model of communication and persuasion (Saleh and Saleh, 2016); the Ulrich model of HR department roles (Voermans and van Veldhoven, 2007;Panos and Bellou, 2016;Noutsa et al, 2017): the Information Systems success model of Delone and MacLean (Kolatshi, 2017;Noutsa et al, 2017;Bayraktaroglu et al, 2019) and the Haines and Petit explanatory model of HRIS success (Bamel et al, 2014;Noutsa et al, 2017). On the other hand, some authors have added explanatory variables to these two models, such as motivation (Yoo et al, 2012), emotional state (Harindran and Jawahar, 2016), the user's country (Amiel and Van De Leemput, 2014) and the impact of linguistic normalisation (Heikkil and Smale, 2011).…”
Section: Synthesis Of the Principal Variables Of Interest For Studying The Acceptance Of Human Resource Information Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated by Tables 1, 2, in the context of HRIS, the TAM and UTAUT models have been combined with others including, for example, the Yale model of communication and persuasion (Saleh and Saleh, 2016); the Ulrich model of HR department roles (Voermans and van Veldhoven, 2007;Panos and Bellou, 2016;Noutsa et al, 2017): the Information Systems success model of Delone and MacLean (Kolatshi, 2017;Noutsa et al, 2017;Bayraktaroglu et al, 2019) and the Haines and Petit explanatory model of HRIS success (Bamel et al, 2014;Noutsa et al, 2017). On the other hand, some authors have added explanatory variables to these two models, such as motivation (Yoo et al, 2012), emotional state (Harindran and Jawahar, 2016), the user's country (Amiel and Van De Leemput, 2014) and the impact of linguistic normalisation (Heikkil and Smale, 2011).…”
Section: Synthesis Of the Principal Variables Of Interest For Studying The Acceptance Of Human Resource Information Systemsmentioning
confidence: 99%
“…In fact, the quality and wealth of the data contained in the HRIS influences its perceived usefulness, perceived ease of use and intention of use (Huang and Martin-Taylor, 2013;Kamaludin and Kamaludin, 2017;Kolatshi, 2017;Udekwe et al, 2017). Among the characteristics of the technology, the overall quality of the computer system (Noutsa et al, 2017;Bayraktaroglu et al, 2019), its security (Saleh and Saleh, 2016;Udekwe et al, 2017) and its processing speed (Huang and Martin-Taylor, 2013;Bamel et al, 2014;Saleh and Saleh, 2016; ) are linked to intention of use and its usual predictors. Consequently, we propose to consider most particularly in the analysis of the acceptance of HRIS the quality of information contained in the system, its security and speed of response, as these dimensions present congruent results in at least two studies.…”
Section: Synthesis Of the Principal Variables Of Interest For Studying The Acceptance Of Human Resource Information Systemsmentioning
confidence: 99%
“…E-HRM is an integrated system covers a whole range of HR activities for the HR department. Usually, e-HRM contains some applications of labor force planning, supply and demand forecast, staffing information, applicant qualifications, information on training and development, salary forecast, pay increase, labor/employee relations, promotion-related information and so on (Bamel et al, 2014). Recent studies also confirmed that e-HRM improves the strategy formulation and decision making for HR activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies on information technology adoption and implementation have indicated difficult technologies, like human resources information systems applications, perceived obstacles are relevant as a result of the adoption method tends to . Shine et al (2015) in his study revealed many challenges that hinder human resource information system implementation effectively Nisha et al (2014) examined university teaching staff's perception regarding many issues such as functions, benefits and barriers of human resource information system .The research results revealed that human resources information are used for administrative purpose. Sabrina (2014) who has analyzed the small corporate houses and big organizations, failed to realize the benefits of HRIS.…”
Section: Literature Reviewmentioning
confidence: 99%